Synthesis of Superabsorbent Polymer (SAP) via Industrially Preferred Route - R. Ahmed; K. Ali Syed (Journal of Basic & Applied Sciences, 2016)
The assigned study is dedicated to the synthesis, improvement and characterization of acrylic-based superabsorbent polymers (SAPs) which can be used in versatile applications notably in disposable diapers and pharmaceutics. The industrially preferred solution polymerization route and low cost monomers were used to synthesize SAPs. Homopolymer and copolymer based SAPs were prepared with varying amount of cross-linker and initiator concentrations and compared for swelling rate with a commercially available SAP sample. Swelling capacity linearly decreases with increase in cross-linker content for both the synthesized SAPs samples whereas it first increases and then decreases with initiator content for the synthesized copolymer SAP. Swelling kinetics of the synthesized and commercial SAPs were modelled using model equation proposed by Omidian et al. Both the synthesized SAPs showed substantial increase in swelling capacity whereas copolymer SAP exhibited the highest swelling rate (rate parameter 2.78 min) when compared to homopolymer SAP and the commercially available SAP samples. Accordingly, the copolymer SAP may find its application in disposable diapers or pharmaceutics where the higher swelling rate is of prime importance. Copolymer and commercially available SAPs depicted significant decrease in swelling capacity even at very low saline solution concentration (0.01 %).